Immunity to the 60kD heat shock proteins: consequences for reproductive outcome - Neuer, Andreas (Brazilian Journal of Sexually Transmitted Diseases, 1998)
A brief revicw on the role of the heat shock proteins (hsp), theircommon properties and possible consequences forearly pregnancy development is described. The 60kD hsp plays an important role as immunogenic antigen of many microbial pathogens and possibly in postinfectious autoimmuniry. The immune responce to hsp may cause pregnancy failure. The consequences of previous sensitization to microbial hsp and the effects of human autoamibodies to hsp. are demonstrated in a mouse embryo culture model.